Cross-country learning in public procurement: An exploratory study. Issue 4 (1st April 2017) - Nijboer, Kimberly; Senden, Shirin; Telgen, Jan
Abstract : All countries use public procurement to some degree to further policy objectives such as sustainability, innovation, fighting fraud and corruption, value for taxpayers' money etc. Countries may learn from past successes and failures in other countries while implementing these policies: cross-country learning. In this exploratory study, we investigate cross-country learning across two frequently used policy areas: sustainability and innovation. A threefold methodology was used that consisted of (1) an extensive review of scientific literature complemented by (2) a thorough examination of policy documents and (3) interviews with leading public procurement experts from 10 countries including both developing and developed countries. The main findings indicate that there is no hard evidence for cross-country learning. Even if cross-country learning would exist, the lessons learned seem to remain largely implicit.